Basal cell papilloma of the external auditory canal: a case report - Anuar, Khairullah (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Basal cell papilloma are benign neoplastic lesion affecting skin, oral mucosa, trunk and genital organs. However it is uncommon to originate in the external auditory canal.We present a 32-year old female presented with otalgia, reduced hearing and bleeding intermittently from the left ear. Clinically it showed multilobulated, blackish mass obliterating the external auditory canal. The mass was friable and bleed to touch. Excision biopsy was done under general anaesthesia and she had uneventful recovery. The histopathology reported as seborrhoeic keratosis or Bbasal cell papilloma. No dysplasia or malignancy seen. In conclusion, basal cell papilloma of the external auditory canal is rare and complete excision of the lesion ensures good outcome and recovery.